PRAKTIK KEPEMIMPINAN ISLAM (Studi Kasus pada Kepala Bagian Non Medis Rumah Sakit Roemani Muhammadiyah Semarang) - Raharjani, Dyah Safitrie; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2017)
In Islam, mankind are the leader of themself, and hold the responsibility of their leadership. Leadership known as a ghairu mahdah worship, thus should be guided by Al Quran and Hadist on its practice. Roemani Muhammadiyah hospital is the one and only Muhammadiyah hospital in Semarang. Muhammadiyah is an organization that practices the teachings of the Prophet Muhammad SAW. It is certain that the application of Islamic value is present in the hospital. The aim of this study is to analyze the extent to which the following participants appliying Islamic values in leadership functions in the Islamic company. The method used is a qualitative method with case study approach, which data collection conducted by interview, observation, and documentation for certain period. Method selected by reason so that the study can be done with focus andÂ depth to determine Islamic leadership practiced by the non-medic heads of divisions in Roemani Muhammadiyah hospital, Semarang.The result shows the outlines of Islamic values, applicated and always maintained by the heads of the divisions on their leadership. The Islamic values such as fatanah, amanah, siddiq, and tabligh are showed in the ledership functions as a model, path finder, aligner, and empowerer.